Identification of very small open reading frames in the genomes of Holmes Jungle virus, Ord River virus, and Wongabel virus of the genus Hapavirus, family Rhabdoviridae. (10th July 2017) - Gubala, Aneta; Walsh, Susan; McAllister, Jane; Weir, Richard; Davis, Steven; Melville, Lorna; Mitchell, Ian; Bulach, Dieter; Gauci, Penny; Skvortsov, Alex; Boyle, David
Viruses of the family Rhabdoviridae infect a broad range of hosts from a variety of ecological and geographical niches, including vertebrates, arthropods, and plants. The arthropod-transmitted members of this family display considerable genetic diversity and remarkable genomic flexibility that enable coding for various accessory proteins in different locations of the genome. Here, we describe the genome of Holmes Jungle virus, isolated from Culex annulirostris mosquitoes collected in northern Australia, and make detailed comparisons with the closely related Ord River and Wongabel viruses, with a focus on identifying very small open reading frames (smORFs) in their genomes. This is the first systematic prediction of smORFs in rhabdoviruses, emphasising the intricacy of the rhabdovirus genome and the knowledge gaps. We speculate that these smORFs may be of importance to the life cycle of the virus in the arthropod vector.